BIBO Stability Analysis for Delay Switched Systems with Nonlinear Perturbation - Jincheng Wei; Peng Shi; Hamid Reza Karimi; Bo Wang (Abstract and Applied Analysis)
The problem of bounded-input bounded-output (BIBO) stability is investigated for a class of delay switched systems with mixed time-varying discrete and constant neutral delays and nonlinear perturbation. Based on the Lyapunov-Krasovskii functional theory, new BIBO stabilization criteria are established in terms of delay-dependent linear matrix inequalities. The numerical simulation is carried out to demonstrate the effectiveness of the results obtained in the paper.